Mesenchymal Stem Cells (MSCs) as a potential therapeutic Strategy in COVID-19 Patients: Literature Research - Coelho, André (2021)
In 2019, an outbreak of an unknown coronavirus – SARS-CoV-2 – responsible for COVID-19 disease, was first reported in China, and evolved into a pandemic of huge dimensions and raised serious concerns for global health. The number of critical cases continues to increase dramatically, while vaccines and specific treatments are not yet available. There are several strategies currently being studied for the treatment of adverse symptoms of COVID-19, that encompass Acute Lung Injury (ALI)/Acute Respiratory Distress Syndrome (ARDS), extensive pulmonary inflammation, cytokine storm, and pulmonary edema, due to virus-induced pneumonia.